Extreme cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: Outcomes from a single tertiary center. (September 2015) - Berger, Yaniv; Aycart, Samantha; Mandeli, John P.; Heskel, Marina; Sarpel, Umut; Labow, Daniel M.
Abstract Background Multivisceral resection as part of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) may be required in order to achieve optimal debulking. This study aimed to assess perioperative and long-term outcomes of the most extensive CRS/HIPEC procedures. Methods All patients who underwent CRS/HIPEC at our institution between March 2007 and July 2014 were retrospectively reviewed. Patients undergoing extreme cytoreduction (n = 50), defined as a resection of ≥5 organs or ≥3 bowel anastomoses, were compared with patients who underwent less extensive procedures (n = 219). Results Complete cytoreduction (CC score ≤1) was achieved in 76% of the extreme CRS/HIPEC group, which included patients with colorectal cancer (CRC, n = 17), appendiceal adenocarcinoma (n = 20), gastric cancer (n = 6), and low-grade appendiceal neoplasm (n = 3). When compared with other patients undergoing CRS/HIPEC, the extreme CRS/HIPEC group had higher median PCI score, increased intraoperative blood loss, longer duration of surgery and longer hospital stay (all p values < 0.001). Major 30-day morbidity was significantly higher among the extreme CRS/HIPEC group (34% vs. 17.4%, p = 0.008) and there was also a trend towards higher 90-day mortality (12% vs. 5.1%, p = 0.07). Median disease free survival and overall survival in CRC patients undergoing extreme CRS/HIPEC was poorer (4.1 vs. 14.3 months, p = 0.01 and 10.1 vs. 43.8 months, p < 0.001, respectively). Extreme CRS/HIPEC was found to independently predict decreased overall survival in CRC patients. Conclusions Extreme multivisceral resection as part of CRS/HIPEC is associated with higher major morbidity and inferior oncologic outcomes; therefore CRS/HIPEC provides the best outcomes in patients with fewer organs involved.